Pembelajaran Syarah / S.K. Kochhar ; editor , A. Ariobimo Nusantara ; penerjemah, H. Purwanto, Yovita Hardiwati - Kochhar , S.K; Nusantara, A. Ariobimo. Purwanto, H. Hardiwati, Yovita (Grasindo, 2008)
xviii, 637 hlm. : Ilus. ; 21 cm.